Is desiccation tolerance and avoidance reflected in xylem and phloem anatomy of two coexisting arid‐zone coniferous trees?. (10th May 2018) - Sevanto, Sanna; Ryan, Max; Dickman, L. Turin; Derome, Dominique; Patera, Alessandra; Defraeye, Thijs; Pangle, Robert E.; Hudson, Patrick J.; Pockman, William T.
Abstract: Plants close their stomata during drought to avoid excessive water loss, but species differ in respect to the drought severity at which stomata close. The stomatal closure point is related to xylem anatomy and vulnerability to embolism, but it also has implications for phloem transport and possibly phloem anatomy to allow sugar transport at low water potentials. Desiccation‐tolerant plants that close their stomata at severe drought should have smaller xylem conduits and/or fewer and smaller interconduit pits to reduce vulnerability to embolism but more phloem tissue and larger phloem conduits compared with plants that avoid desiccation. These anatomical differences could be expected to increase in response to long‐term reduction in precipitation. To test these hypotheses, we used tridimensional synchroton X‐ray microtomograph and light microscope imaging of combined xylem and phloem tissues of 2 coniferous species: one‐seed juniper ( Juniperus monosperma ) and piñon pine ( Pinus edulis ) subjected to precipitation manipulation treatments. These species show different xylem vulnerability to embolism, contrasting desiccation tolerance, and stomatal closure points. Our results support the hypothesis that desiccation tolerant plants require higher phloem transport capacity than desiccation avoiding plants, but this can be gained through various anatomical adaptations in addition to changing conduit or tissue size. Abstract : Stomatal closure point during drought is related to xylem anatomy and vulnerability to embolism, but little is known about how stomatal closure point and the need to transport sugars at low tissue water potentials affects the phloem. We used tridimensional synchroton X‐ray microtomograph and light microscope imaging of combined xylem and phloem tissues of 2 coniferous species that show contrasting desiccation tolerance and stomatal closure points to test recent theoretical hypotheses about the changes needed in phloem anatomy to allow sugar transport at low water potentials. Our results support the hypothesis that plants operating at low water potentials require higher phloem transport capacity than plants that maintain relatively high water potentials, but the high transport capacity can be gained through various anatomical adaptations in addition to changing conduit or tissue size.